Honey, baby, mine [large type] : a mother and daughter talk life, death, love (and banana pudding) - Dern, Laura; Ladd, Diane (Grand Central Large Print, 2023)
A collection of personal conversations from the actress and mother-daughter duo covers topics from ambition and legacy to intimacy, love, success, and marriage.